MDMA-assisted psychotherapy; Inclusion of transgender and gender diverse people in the frontiers of PTSD treatment trials - Stauffer, Christopher S.; Brown, Melanie R.; Adams, Dee; Cassity, Marca; Sevelius, Jae (Frontiers in Psychiatry, 2022)
Introduction Transgender and gender diverse (TGD) people experience stigma, discrimination, trauma, and post-traumatic stress disorder (PTSD) at higher rates compared to the general population; however, TGD people have been underrepresented in PTSD research. Clinical trials of 3,4-methylenedioxymethamphetamine (MDMA)-assisted psychotherapy demonstrate promising safety and efficacy for the treatment of PTSD. Issues related to equitable access, power imbalances in the therapeutic relationship, and vulnerable states of consciousness occasioned by MDMA are magnified when working with people affected by structural vulnerabilities and health disparities, and community engagement in research planning and implementation is essential. To inform the inclusion and safety of TGD people in future MDMA-assisted psychotherapy research, the aims of the current study were to: characterize TGD experiences with trauma-related mental health care, assess openness of TGD people to participate in experimental PTSD research, and to gather specific feedback on protocol design for conducting MDMA-assisted psychotherapy with TGD people. Materials and methods We conducted three virtual focus group discussions (FGDs) with 5–6 participants each (N = 17). Eligible TGD participants had a history of receiving trauma-related mental health care. Each FGD was facilitated by two licensed clinicians who identified as TGD. Qualitative data analysis was conducted via an iterative process of identification of recurrent patterns and themes. Results We have identified several key issues TGD people face when seeking and engaging in trauma-related mental health care, including barriers to receiving adequate gender-affirming and trauma-informed mental health care and frustration with providers lacking cultural humility. Suggested amendments to MDMA-assisted psychotherapy protocols include: routine collection of trans-inclusive gender identity data, implementing an explicit gender-affirming treatment approach, ensuring a culturally safe setting, and diversifying co-therapy dyads. Discussion The inclusion of TGD voices in early conversations about emerging experimental PTSD interventions promotes equitable access, in the context of health and healthcare disparities, and helps researchers understand the needs of the community and tailor research to meet those needs. Through an ongoing conversation with the TGD community, we aim to incorporate a gender-affirming approach into existing research protocols and inform future applications of MDMA-assisted psychotherapy in addressing the effects of minority stress and boosting resilience.